Rol de enfermería en cuidados paliativos dirigido al cuidador del paciente en etapa terminal, Unidad Anidada San Vicente de Paúl, Pasaje, El Oro, octubre 2018 - abril 2019 - Mendoza Bustos, Yislaine Yomira (2019)
Nursing is part of the multidisciplinary team that is focused and oriented to provide palliative care, because it has knowledge about the activities that must be fulfilled and its main function is to educate the caregiver about the management and control of symptoms that the patient may experience patient, but the problem is that the caregiver does not have the necessary knowledge so that from home he can provide a good integral assistance that allows to improve the quality of life of the patient until his last days. The objective of this research is to determine the role of nursing in palliative care directed to the patient's caregiver in the terminal stage of the Nest Unit San Vicente de Paúl, Pasaje, El Oro, October 2018 - April 2019. The present study has a qualitative and quantitative approach, through a descriptive and bibliographical investigation, applying the inductive-deductive methods, with the use of the survey technique through a structured questionnaire. The results obtained through the survey of the 30 caregivers of the terminally ill patients and the 4 nurses, allowed us to reach the following conclusions that cancer is the disease that is most often seen in the San Vicente de Paúl Unit. Caregivers do not have the knowledge about hygiene measures and how to administer medications by subcutaneous route, nor does it have a palliative care guide that guides them to provide quality care to the terminal patient